2015
DOI: 10.3892/ol.2015.3091
|View full text |Cite
|
Sign up to set email alerts
|

S100B-p53 disengagement by pentamidine promotes apoptosis and inhibits cellular migration via aquaporin-4 and metalloproteinase-2 inhibition in C6 glioma cells

Abstract: Abstract. S100 calcium-binding protein B (S100B) is highly expressed in glioma cells and promotes cancer cell survival via inhibition of the p53 protein. In melanoma cells, this S100B-p53 interaction is known to be inhibited by pentamidine isethionate, an antiprotozoal agent. Thus, the aim of the present study was to evaluate the effect of pentamidine on rat C6 glioma cell proliferation, migration and apoptosis in vitro. The change in C6 cell proliferation following treatment with pentamidine was determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 37 publications
(43 reference statements)
1
26
0
Order By: Relevance
“…Cell apoptosis is regulated by a set of genes and is accompanied by changes in the expression of associated proteins [ 22 ], so we further investigated the anti-apoptotic function of Uc.173 at the protein level. The cascade reaction induced by the caspase cysteine protease family is the key event in the process of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Cell apoptosis is regulated by a set of genes and is accompanied by changes in the expression of associated proteins [ 22 ], so we further investigated the anti-apoptotic function of Uc.173 at the protein level. The cascade reaction induced by the caspase cysteine protease family is the key event in the process of cell apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…There is a renewed interest in pentamidine, an antiprotozoal drug discovered in 1938 for treatment of Pneumocystis jirovecii pneumonia, due to the recent discovery of its anti-inflammatory and neuroprotective effect in Alzheimer’s disease (AD) [ 14 , 15 , 16 ]. It is suggested that pentamidine inhibits S100 calcium-binding protein B (S100B) in glial cells by blocking interaction between S100B and tumor suppressor p53.…”
Section: Introductionmentioning
confidence: 99%
“…It is suggested that pentamidine inhibits S100 calcium-binding protein B (S100B) in glial cells by blocking interaction between S100B and tumor suppressor p53. Overexpression of S100B protein is responsible for upregulation of cell apoptosis and neuroinflammation, which is a key feature of AD [ 15 , 16 ]. The progression of AD could be delayed with anti-inflammatory and antiproliferative effects of pentamidine.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, we demonstrated that pentamidine inhibited other proinflammatory events like lipid peroxidation and nitric oxide release. According to our previous observations [ 29 ], S100B protein release was upregulated by A β injection but its level was not affected by pentamidine treatment. To prove that all the above discussed anti-inflammatory effects, together with the reduction of reactive gliosis, were due to the inhibition of S100B/p53 binding, we evaluated p53 expression in the different experimental conditions.…”
Section: Discussionmentioning
confidence: 66%
“…Here we show that pentamidine, an ancient antiprotozoal drug that inhibits S100B protein, ameliorates gliosis and neuroinflammation in a mouse model of A β -induced AD. Many studies have been addressed in the attempt to enlarge the pharmacological knowledge on pentamidine and its novel therapeutic effects in disorders characterized by S100B upregulation, such as melanoma [ 28 ], glioblastoma [ 29 ], and colitis [ 19 ]. This has led to the discovery that, besides being an antiprotozoal drug, pentamidine also inhibits S100B activity by blocking the interaction at the Ca ++ /p53 site of the protein.…”
Section: Discussionmentioning
confidence: 99%